University Campus information system to assess quality of life using users' perception : a case study applied on the University of Minho Campus - Rodrigues, Daniel Souto (2008)
Nowadays, quality of life survey is one of the primary concerns in urban planning and management. Its evaluation and monitoring became a challenge that decision makers have to lead with. This paper presents the work that conduced to the development of an information system to evaluate and monitor university campi quality of the life. The system embodies two main functions: to inform, allowing any user to know how has evolved the quality of life on campus; to be a decision support tool, mainly for facilities planning and management, taking advantages of users participation, through individual evaluations, in getting a global quality of life users perception. The results of the application of that system in case study are also presented.